2016
DOI: 10.1111/nyas.13140
|View full text |Cite
|
Sign up to set email alerts
|

Early adverse experience and substance addiction: dopamine, oxytocin, and glucocorticoid pathways

Abstract: Substance addiction may follow a chronic, relapsing course and critically undermine the physical and psychological well-being of the affected individual and the social units of which the individual is a member. Despite the public health burden associated with substance addiction, treatment options remain suboptimal, with relapses often seen. The present review synthesizes growing insights from animal and human research to shed light upon developmental and neurobiological pathways that may increase susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 211 publications
(408 reference statements)
1
45
1
2
Order By: Relevance
“…This is consistent with the notion that substance use compromises maternal behavior by co‐opting the mesocorticolimbic DA system and disrupting naturally occurring OT‐related neuroadaptations [Rutherford et al, ; Strathearn and Mayes, ]. Alternatively, dysregulations of the OT‐ and DA‐systems may have already been present in susceptible mothers even prior to the onset of addiction [Buisman‐Pijlman et al, ; Kim et al, ]. In this case, the same neurobiological mechanisms that increase the mother's susceptibility to addiction may also undermine her reward response to her infant and may have contributed to the pattern of findings reported here.…”
Section: Discussionmentioning
confidence: 86%
“…This is consistent with the notion that substance use compromises maternal behavior by co‐opting the mesocorticolimbic DA system and disrupting naturally occurring OT‐related neuroadaptations [Rutherford et al, ; Strathearn and Mayes, ]. Alternatively, dysregulations of the OT‐ and DA‐systems may have already been present in susceptible mothers even prior to the onset of addiction [Buisman‐Pijlman et al, ; Kim et al, ]. In this case, the same neurobiological mechanisms that increase the mother's susceptibility to addiction may also undermine her reward response to her infant and may have contributed to the pattern of findings reported here.…”
Section: Discussionmentioning
confidence: 86%
“…Neuroscience research is shedding light on neuroendocrine mechanisms through which early exposure to childhood maltreatment may lead to an increased risk for substance abuse. This may include changes in glucocorticoid stress response systems, oxytocin systems relating to social impairment, and dopamine-related reward sensitivity, each of which may differ based on gender (Kim et al, 2016). Maltreated individuals who inject drugs may also have multiple other risk factors including polysubstance use (Markowitz et al, 2011; Ompad et al, 2005), being victim and perpetrator of violence experiences (Lake et al, 2015) and HIV risk behaviours (Kang et al, 2002; Lee et al, 2015; Markowitz et al, 2011; Ompad et al, 2005), as well as poor adherence to medications (Markowitz et al, 2011) and perceived abuse in healthcare settings (Palis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Prevention of childhood maltreatment and trauma informed care (Raja, Hasnain, Hoersch, Gove-Yin, & Rajagopalan, 2015) may provide a venue for intervening to reduce the long-term impacts of injecting drug use in young adults. The latter involves understanding possible developmental pathways from childhood maltreatment victimization to neurobiological impairments and subsequent substance use disorders (Kim et al, 2016). Also, the findings may help provide appropriate treatment for injecting drug use among the maltreated people including social support (Murray, Nguyen, & Cohen, 2014) and cognitive-based psychotherapy (Gilbert et al, 2009; MacMillan et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that sustained increases in CRH levels during pregnancy, reduced sensitivity of anterior pituitary receptors and mild suppression of cortisol in the postpartum period may be potential contributors to this discrepancy, although the specific mechanisms behind this discrepancy need to be addressed further in future research. Despite the well‐established associations between early adversity, HPA axis functions and a range of psychiatric disorders, no study has yet directly examined the role of early adversity as it relates to the cortisol‐PPD relationship discussed here. However, a study examining high‐risk postpartum mothers with a lifetime history of MDD demonstrated that subclinical symptoms of depression in these mothers moderated the relationship between mothers’ early‐life trauma and their cortisol reactivity.…”
Section: Maternal Hormones In Postpartum Depressionmentioning
confidence: 99%